2001
DOI: 10.1097/00006534-200103000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of Keloid-Derived Keratinocytes on Fibroblast Growth and Proliferation in Vitro

Abstract: Keloids are disfiguring, proliferative scars that represent a pathological response to cutaneous injury. The overabundant extracellular matrix formation, largely from collagen deposition, is characteristic of these lesions and has led to investigations into the role of the fibroblast in its pathogenesis. Curiously, the role of the epidermis in extracellular matrix collagen deposition of normal skin has been established, but a similar hypothesis in keloids has not been investigated. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
92
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 23 publications
9
92
0
Order By: Relevance
“…Using keratinocyte and fibroblast cell strains from these samples, we have demonstrated, for the first time, differences between normal and keloid fibroblast collagen response to coculture with normal or keloid keratinocytes. Normal and keloid keratinocytes, like normal and keloid fibroblasts, also appear to be distinct subtypes from these observed differences, which reinforces earlier work (23) suggesting the role of epithelial-mesenchymal interactions in keloid pathogenesis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using keratinocyte and fibroblast cell strains from these samples, we have demonstrated, for the first time, differences between normal and keloid fibroblast collagen response to coculture with normal or keloid keratinocytes. Normal and keloid keratinocytes, like normal and keloid fibroblasts, also appear to be distinct subtypes from these observed differences, which reinforces earlier work (23) suggesting the role of epithelial-mesenchymal interactions in keloid pathogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, using an in vitro two-chamber coculture model, we showed that normal dermal fibroblast proliferation was significantly increased when cocultured with keloid-derived keratinocytes (which we propose to be called "keloid keratinocytes") in a serum-free medium (23). These data suggested that soluble factors promoting fibroblast proliferation were elaborated by keloid keratinocytes in a manner different from normal skin-derived keratinocytes (termed "normal keratinocytes").…”
mentioning
confidence: 93%
“…Greater thickness of neodermis production was seen in fibroblast-seeded skin models when keratinocytes from hypertrophic scars were added in culture (32). Similar results were detected with coculturing of keloidderived keratinocytes and fibroblasts (62), suggesting that keratinocytes might have an important role in keloid and hypertrophic scar pathogenesis by producing signals that stimulate the fibroblasts in the underlying dermis to proliferate or produce more ECM. The basis for an inherent abnormality among hypertrophic scar and keloid-derived keratinocytes remains elusive, however.…”
Section: Fibrogenic Responsesupporting
confidence: 60%
“…Passage 2 KK and fibroblasts were isolated from excised earlobe keloid samples as previously described (31). Normal keratinocytes (NK) and NF were randomly derived from a bank of foreskin circumcision specimens of healthy young children, again as previously described (31).…”
Section: Methodsmentioning
confidence: 99%
“…We extrapolated this concept of epithelial-mesenchymal interactions to keloids in two recent in vitro studies examining the possible effects of such interactions on normal fibroblasts (NF) in serum-free, two-chamber coculture with normal or keloid-derived keratinocytes (KK). We demonstrated significantly higher rates of proliferation (31), as well as a significant increase in soluble extracellular-matrix collagen production by NF cocultured with KK (30a).…”
mentioning
confidence: 87%